2019
DOI: 10.1159/000497315
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy in the Elderly: Do Radiological and Clinical Outcomes Differ from Those in Younger Patients? A Prospective Single-Center Experience

Abstract: Objectives: Endovascular treatment (EVT) has emerged as the gold standard therapy for stroke due to large vessel occlusion (LVO). There is however limited evidence to suggest that similar efficacy can be expected in elderly patients. We aimed to assess the efficacy and safety of EVT in elderly patients (aged > 80), comparing outcomes to younger patients (aged < 80). Material and Methods: A total of 195 patients with LVO stroke treated with EVT were included and dichotomized by age. We compared neurological imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Our centre has always maintained a policy of open inclusion criteria, not selecting patients based on their age or excluding patients based on strict imaging criteria. This policy has not only been reinforced by our own experiences, 13 but is also reflected in age dichotomized sub analyses of HERMES 18 . Despite the inclusion of a significantly higher number of octogenarians, clinical outcomes were in line with those in the randomized controlled trials 19,20,23 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our centre has always maintained a policy of open inclusion criteria, not selecting patients based on their age or excluding patients based on strict imaging criteria. This policy has not only been reinforced by our own experiences, 13 but is also reflected in age dichotomized sub analyses of HERMES 18 . Despite the inclusion of a significantly higher number of octogenarians, clinical outcomes were in line with those in the randomized controlled trials 19,20,23 …”
Section: Discussionmentioning
confidence: 82%
“…Patients in whom EVT was performed twice due to a recurring cerebrovascular event during the same hospital admission or patients transferred to another hospital were excluded from analyses (4 EVT procedures). Detailed inclusion criteria from our centre are outlined in a previous publication, 13 and in contrast to the randomized controlled studies, we had no upper age limit, included tandem and basilar occlusions, and had liberal inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, the meta‐analysis concluded that EVT is of benefit across a wide range of age including octogenarians. We have previously shown that elderly stroke patients presenting with LVO stroke have a similar early neurological improvement; however, their functional outcomes are worse as compared to those aged <80 6 . A recent meta‐analysis confirmed this finding, where successful recanalization rates and symptomatic intracerebral bleeding (sICH) rates were similar, a significantly lower proportion of the elderly achieved a good clinical outcome at 3 months 7 .…”
Section: Introductionmentioning
confidence: 76%
“…All procedures were performed in a monoplane angiography suite equipped with a Siemens Artis zee (December 2009–June 2014) or a Philips Allura FD20 Clarity (Philips, Best; Netherlands) (June 2014–to date). Interventional details are described earlier 6 . Most of the procedures in the first years of the study were performed under general anesthesia, in later years conscious sedation was preferred 8 …”
Section: Methodsmentioning
confidence: 99%
“…Realworld experience of patients undergoing MT over 80 years of age revealed a good functional outcome in 21% and a higher rate of intracranial hemorrhage than younger patients (59). Mortality in patients over 80 is significantly higher than younger patients (33 vs. 14%) (60). Patients over 80 years of age also have high rates of futile reperfusion (50%) (61).…”
Section: Acute Stroke Care Considerationsmentioning
confidence: 99%